Interplay Between Calcium and AMPK Signaling in Human Cytomegalovirus Infection - Dunn, Diana M.; Munger, Joshua (Frontiers in Cellular and Infection Microbiology, 2020)
Calcium signaling and the AMP-activated protein kinase (AMPK) signaling network broadly regulate numerous aspects of cell biology. Human Cytomegalovirus (HCMV) infection has been found to actively manipulate the calcium-AMPK signaling axis to support infection. Many HCMV genes have been linked to modulating calcium signaling, and HCMV infection has been found to be reliant on calcium signaling and AMPK activation. Here, we focus on the cell biology of calcium and AMP-activated protein kinase (AMPK) signaling and what is currently known about how HCMV modulates these pathways to support HCMV infection and potentially contribute to oncomodulation.